Pengaruh Tingkat Pendidikan, Pemahaman Teknologi Informasi, dan Ukuran Usaha terhadap Penerapan SAK EMKM pada UMKM Kafe di Surabaya - Sylvia Martha; Tantina Haryati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This research aims to test and analyze the influence of education level, understanding of information technology, and business size on the application of SAK EMKM to MSMEs Café in Surabaya. The population used in this study of café MSME owners was 652 based on data from the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia. This research is quantitative research. The study used primary data in the form of questionnaires. Sampling techniques use random sampling methods. Based on established criteria or considerations obtained by 100 café owners as a research sample. The analysis techniques in this study used partial least square with the help of the SmartPLS program. The results of this study show that the Level of Education Affects the Application of SAK EMKM in Café MSMEs in Surabaya, Understanding Technology Does Not Affect the Application of EMKM SAK in Café MSMEs in Surabaya., Business Size Affects the Application of SAK EMKM in MSMEs Café in Surabaya. Keywords: Level of Education; Understanding Technology; Business Size; SAK EMKM; MSMEs Education Level; Understanding Technology; Business Size; SAK EMKM; UMKM